Enjoyment Perception during Exercise with Aerobic Machines. Issue 1 (August 2014) - Carraro, Attilio; Gobbi, Erica; Ferri, Ilaria; Benvenuti, Paolo; Zanuso, Silvano
This study investigated enjoyment and naturalness of movement perceived during short bouts of exercise with three aerobic machines: treadmill, elliptical crosstrainer, and Vario. The participants were 72 experienced and 60 inexperienced users. Immediately after the exercise with each machine, they filled in a 12-item form of the Physical Activity Enjoyment Scale (PACES) and a Visual Analogue Scales (VAS) about naturalness of movement. Results showed significant within-subjects differences on all scales; exercise with the treadmill and Vario were perceived to be similarly enjoyable and more enjoyable and natural in comparison with the elliptical crosstrainer. Differences in naturalness ratings between experienced and inexperienced users were observed. Exercise was not equally enjoyable when performed with different aerobic machines, and this should be considered by professionals when prescribing aerobic training to enhance motivation and adherence.